Postharvest Treatments with Methyl Jasmonate and Salicylic Acid for Maintaining Physico-Chemical Characteristics and Sensory Quality Properties of Apricot Fruit during Cold Storage and Shelf-Life - Ezzat Ahmed; Ammar Amin; Szabó Zoltán; Nyéki József; Holb Imre J. (Polish Journal of Food and Nutrition Sciences)
The aim of this study was to investigate the effect of methyl jasmonate and salicylic acid on 12 quality parameters of apricot fruit in treatments of cold storage (1°C for 7, 14 and 21 days) and shelf-life (4 and 8 days at 25°C after a 21-day cold storage treatment). Fruit quality parameters included 6 physico-chemical characteristics (weight loss, fruit firmness, total soluble solids, acidity, total soluble solids/acidity ratio and juice pH) and 6 sensory properties (skin and flesh colour, texture, taste, visual appearance and overall acceptability). Among physico-chemical characteristics, applications of 0.2 mmol/L methyl jasmonate and 2 mmol/L salicylic acid significantly reduced fruit weight loss, fruit softening and juice pH and maintained soluble solid content and acidity over the whole storage period. Among sensory properties, all parameters were generally increased by methyl jasmonate and salicylic acid treatments compared to water-treated control and the water-treated fruits showed the lowest scores below the acceptability limit except for skin colour. In conclusion, our results suggest using methyl jasmonate and/or salicylic acid to enhance and prolong the storability of apricot fruits during both cold storage and shelf-life period.